Challenges in implementing the participatory rubber replanting model in Indonesian rubber smallholdings - Supriadi M (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.210-222.)
Replanting program will be the key strategy to help improve the condition of rubber smallholdings in Indonesia for the following reasons namely: 1. In the traditional rubber area there is a lack of a suitable land for new planting development due to the competition with other crops and industry, 2. there is a high proportion of old and unproductive rubber area and a low adoption of rubber clones and other recommended technologies that have resulted in the low productivity of rubber smallholdings. Replanting movement is also an entry point towards the adoption of rubber technologies by farmers. The challenge in managing rubber replanting program is how to select the replanting model/schemes for the implementation. Due to the disappointing slow rate rubber development in the past, Indonesian Rubber Research Institute (IRRI) has been promoting the Participatory Rubber Replanting Model that can be used as a framework to help accelerating self-help rubber replanting or development movement in smallholdings sector. This model requires greater self-help community initiatives and broad-based participation of smallholders. Some component programs of the Model have been implemented in three rubber-producing provinces in Indonesia (South Sumatra, Jambi and South Kalimantan). It is indicated from the observation that there will be significant challenges occurred in the implementing of the Participatory Rubber Replanting Model in larger scale. The mentality of dependency of farmers upon government assistance or external resources, an authoritarian attitude of government officers and a rigid adherence to rules and regulations, and weak linkages of related institutions and actors following are some of the barriers that could either impede the adoption of the participatory rubber replanting model or prevent the success of the implementation of the model in the Indonesian situation.
Keywords: Indonesia; Participatory replanting model; Rubber smallholder